Integrating neuroimaging biomarkers into the multicentre, high-dose erythropoietin for asphyxia and encephalopathy (HEAL) trial: rationale, protocol and harmonisation. Issue 4 (22nd April 2021) - Wisnowski, Jessica L; Bluml, Stefan; Panigrahy, Ashok; Mathur, Amit M; Berman, Jeffrey; Chen, Ping-Sun Keven; Dix, James; Flynn, Trevor; Fricke, Stanley; Friedman, Seth D; Head, Hayden W; Ho, Chang Y; et al.
Abstract : Introduction: MRI and MR spectroscopy (MRS) provide early biomarkers of brain injury and treatment response in neonates with hypoxic-ischaemic encephalopathy). Still, there are challenges to incorporating neuroimaging biomarkers into multisite randomised controlled trials. In this paper, we provide the rationale for incorporating MRI and MRS biomarkers into the multisite, phase III high-dose erythropoietin for asphyxia and encephalopathy (HEAL) Trial, the MRI/S protocol and describe the strategies used for harmonisation across multiple MRI platforms. Methods and analysis: Neonates with moderate or severe encephalopathy enrolled in the multisite HEAL trial undergo MRI and MRS between 96 and 144 hours of age using standardised neuroimaging protocols. MRI and MRS data are processed centrally and used to determine a brain injury score and quantitative measures of lactate and n-acetylaspartate. Harmonisation is achieved through standardisation—thereby reducing intrasite and intersite variance, real-time quality assurance monitoring and phantom scans. Ethics and dissemination: IRB approval was obtained at each participating site and written consent obtained from parents prior to participation in HEAL. Additional oversight is provided by an National Institutes of Health-appointed data safety monitoring board and medical monitor. Trial registration number: NCT02811263; Pre-result .